Co-expression of HLA-E and HLA-G on genetically modified porcine endothelial cells attenuates human NK cell-mediated degranulation - Cross-Najafi, Arthur A.; Farag, Kristine; Isidan, Abdulkadir; Li, Wei; Zhang, Wenjun; Lin, Zhansong; Walsh, Julia R.; Lopez, Kevin; Park, Yujin; Higgins, Nancy G.; Cooper, David K.C.; Ekser, Burcin; et al. (Frontiers in Immunology, 2023)
Natural killer (NK) cells play an important role in immune rejection in solid organ transplantation. To mitigate human NK cell activation in xenotransplantation, introducing inhibitory ligands on xenografts via genetic engineering of pigs may protect the graft from human NK cell-mediated cytotoxicity and ultimately improve xenograft survival. In this study, non-classical HLA class I molecules HLA-E and HLA-G were introduced in an immortalized porcine liver endothelial cell line with disruption of five genes (GGTA1, CMAH, β4galNT2, SLA-I α chain, and β-2 microglobulin) encoding three major carbohydrate xenoantigens (αGal, Neu5Gc, and Sda) and swine leukocyte antigen class I (SLA-I). Expression of HLA-E and/or HLA-G on pig cells were confirmed by flow Deleted: Indiana 33 Deleted: four This is a provisional file, not the final typeset article cytometry. Endogenous HLA-G molecules as well as exogenous HLA-G VL9 peptide could dramatically enhance HLA-E expression on transfected pig cells. We found that co-expression of HLA-E and HLA-G on porcine cells led to a significant reduction in human NK cell activation compared to the cells expressing HLA-E or HLA-G alone and the parental cell line. NK cell activation was assessed by analysis of CD107a expression in CD3 -CD56 + population gated from human peripheral blood mononuclear cells. CD107a is a sensitive marker of NK cell activation and correlates with NK cell degranulation and cytotoxicity. HLA-E and/or HLA-G on pig cells did not show reactivity to human sera IgG and IgM antibodies. This in vitro study demonstrated that coexpression of HLA-E and HLA-G on genetically modified porcine endothelial cells provided a superior inhibition in human xenoreactive NK cells, which may guide further genetic engineering of pigs to prevent human NK cell mediated rejection. Deleted: analysis 61 Moved (insertion) [1] Deleted: degranulation 62 Moved up [1]: Endogenous HLA-G molecules as well as 63 exogenous HLA-G VL9 peptide could dramatically enhance HLA-E 64 expression on transfected pig cells.